Innovation In Robotics Toolkit Learning to Foster The Love Of Learning in Young Children - Sri Utaminingsih; Ahmad Abdul Chamid; Akhmad Akhmad (Journal of Primary Education (JPE), 2026)
This research aims to develop a robotics toolkit as an innovative learning medium to foster a love of learning in early childhood. The research method used the Borg & Gall Research and Development (R&D) model, conducted in early childhood education (PAUD) schools. Primary data was obtained from educators, principals, and classroom observations of early childhood education (PAUD) children aged 5-6 years. The preliminary study revealed that 66.6% of educator respondents needed robotics media. The products developed included storybooks, coding puzzle boards, puzzle pieces, and flashcards equipped with audio QR codes, unplugged code-based robotics programming, and a love of learning habits. Field trials demonstrated a very positive response, with 100% of teachers and principals rating the toolkit as easy to use, safe, and developmentally appropriate for early childhood. These findings demonstrate that the robotics toolkit is effective in early childhood education to enhance children's cognitive, social-emotional, and motor skills, but is also relevant as a STEAM-based learning innovation that supports 21st-century skills.